Inflammatory effects of in vivo glycated albumin from cardiovascular patients - Paradela-Dobarro, Beatriz; Bravo, Susana B.; Rozados-Luís, Adriana; González-Peteiro, Mercedes; Varela-Román, Alfonso; González-Juanatey, José Ramón; García-Seara, Javier; Alvarez, Ezequiel (Biomedicine & pharmacotherapy, 2019)
[Display omitted] Characterization of the type of glycation found in circulating proteins from cardiovascular patients in comparison with healthy control subjects and to explore the pathophysiological molecular effects of these glycomodified proteins on human umbilical vein endothelial cells (HUVEC) in culture. Human serum albumin pools from 10 subjects each, of patients with heart failure (HF) presenting high or low glycation levels, and from healthy subjects were isolated and purified. The glycation levels of these pools were characterized by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and compared between them. Analysis of endothelial dysfunction after the treatment of HUVEC with the pools was made by mRNA expression of adhesion molecules and by functional adhesion of mononuclear cells to HUVEC monolayers. Specific characterization of post-transductional modifications (advanced glycation end products) in high and low glycated albumins from patients was made in comparison with healthy subjects. Albumins from patients were able, at very low concentrations (12.5 μg/mL), to significantly up-regulate (˜0.2 – 2 fold) the gene expression of adhesion molecules in HUVEC. At the functional level, the albumin from patients with high glycation levels (at 12.5 and 25 μg/mL) significantly enhanced (˜10%) the adhesion of mononuclear cells to HUVEC. Differences in the glycomodification of albumin from HF patients were found and specifically characterized in comparison with albumin from healthy subjects. Functionally, in vivo glycated albumin in patients with HF induced an increase in adhesion molecules expression on HUVEC, which supported an increase in peripheral blood mononuclear cells adhesion to endothelial cells.